POTENSI TERAPI PROBIOTIK SEBAGAI TERAPI ALZHEIMER MELALUI GUT-BRAIN AXIS - Nafatasya Ayu Rahmansyah (Faculty of Medicine Universitas Mataram, 2022)
ABSTRAK Alzheimer's disease is a neurodegenerative disease characterized by loss of memory and decreased cognitive function. Symptoms of Alzheimer's disease include confusion, incorrect assessment, irritation, withdrawal, and hallucination. Microbiota Gut-Brain Axis (MGBA) is a complex communication system between GIT, gut microbiota and central nervous system that transmits information to and from the brain and used to treat and improve symptoms of mental disorders with probiotic (live bacteria). The Purpose of this review is to determine relationship between the gut-brain axis and probiotic as a treatment for mental disorders. This study is a research with literature study using Google Scholar, PubMed and Science Direct with keywords (Alzheimer's) AND (probiotic AND Alzheimer's). The types of articles used are meta analysis, systematic literature review, narrative review and use Indonesian and English free full text publication between 2012-2022. The final articles selected by the authors were 15 journal articles. The literature study found the long-term benefit of using probiotic that can improve health function and development as well as cognitive maturation and diet therapy as a therapy in Alzheimer's disease. The role of probiotic is to improve function and health development and cognitive maturation. Keywords: Alzheimer’s, Gut-Brain Axis, Probiotics, Diet